How culturally unique are pandemic effects? Evaluating cultural similarities and differences in effects of age, biological sex, and political beliefs on COVID impacts - Conway, Lucian Gideon; Woodard, Shailee R.; Zubrod, Alivia; Tiburcio, Marcela; Martínez-Vélez, Nora Angélica; Sorgente, Angela; Lanz, Margherita; Serido, Joyce; Vosylis, Rimantas; Fonseca, Gabriela; Lep, Žan; Li, Lijun; et al. (Frontiers in Psychology, 2022)
Despite being bio-epidemiological phenomena, the causes and effects of pandemics are culturally influenced in ways that go beyond national boundaries. However, they are often studied in isolated pockets, and this fact makes it difficult to parse the unique influence of specific cultural psychologies. To help fill in this gap, the present study applies existing cultural theories via linear mixed modeling to test the influence of unique cultural factors in a multi-national sample (that moves beyond Western nations) on the effects of age, biological sex, and political beliefs on pandemic outcomes that include adverse financial impacts, adverse resource impacts, adverse psychological impacts, and the health impacts of COVID. Our study spanned nineteen nations (participant N = 14,133) and involved translations into nine languages. Linear mixed models revealed similarities across cultures, with both young persons and women reporting worse outcomes from COVID across the multi-national sample. However, these effects were generally qualified by culture-specific variance, and overall more evidence emerged for effects unique to each culture than effects similar across cultures. Follow-up analyses suggested this cultural variability was consistent with models of pre-existing inequalities and socioecological stressors exacerbating the effects of the pandemic. Collectively, this evidence highlights the importance of developing culturally-flexible models for understanding the cross-cultural nature of pandemic psychology beyond typical WEIRD approaches.